Pembagian Harta Waris Bagi Anak Perempuan Bungsu di Desa Bubak Kabupaten Pekalongan - Hakiki, Nur (Al-Hukkam: Journal of Islamic Family Law, 2021)
Even though the division of inheritance has been determined, in practice there are often inheritances that cannot be settled based on Islamic inheritance but are carried out in ways based on local customary law. This study aims to analyze the background of the youngest daughter getting more inheritance and to find out the view of Islamic law on the distribution of inheritance more for the youngest daughter. This thesis uses qualitative field research methods which are carried out directly in the field so that researchers can obtain information and data as close as possible to the real world. The result of this study is that the distribution of inheritance is more for the youngest daughter in Bubak Village,Kandangserang, Pekalongan Regency, the distribution is using local customary law. In Bubak Village, the youngest daughter gets a higher share of the inheritance than the other children. Theoretically it is not in accordance with the Fiqh of Mawaris Islam, but the people here prioritize the principles of justice, pleasure, sincerity and accept all the results of joint decisions. So that in general the distribution of inheritance in Bubak Village does not violate Islamic law, which aims to prevent disputes and inheritance disputes between families.